Performance Evaluation of Banks Sponsored Mutual Funds: An Analytical Study. Issue 2 (December 2019) - Sharma, Meena; Didwania, Manish; Kumar, D. Suresh
This research paper inspects the comparative performance evaluation of banks sponsored Indian mutual funds using traditional measure. The data comprises 166 open-ended equity, debt, liquid and equity linked saving schemes (tax savings) schemes during the period of April 2006–March 2017. The evidence shows that all sample schemes are well diversified. Public sector banks sponsored get first ranked because good return, all positive and diversified schemes and efficient performance of portfolio management as compared to Private sector and UTI banks sponsored mutual funds.